Unveiling Jane Eyre: space escape and the construction of subjectivity through a Foucauldian lens - Nie, Zhixing; Kaur, Hardev; Mani, Manimangai (UNISA Press, 2024)
This paper reexamines Charlotte Brontë’s Jane Eyre through a Foucauldian lens, focusing on how traditional societal structures and the rise of capitalism impact women in 19th-century Britain, as observed by literary critic Sandra M. Gilbert and Gayatri C. Spivak. It analyses Jane’s journey through oppressive environments such as Gateshead Hall, Lowood School, Thornfield Hall, and Marsh End, culminating in her retreat to Ferndean Manor. These settings are interpreted as sites of power that impose disciplinary measures on Jane, both physically and mentally, with windows symbolising possible escape routes. The study argues that Jane represents a female rebel challenging patriarchal constraints and seeking personal freedom and equality. Despite her attempts to transcend societal and economic confines, her ultimate settlement at Ferndean Manor highlights the persistent influence of the old societal order, illustrating the novel’s realism and the complex, inescapable nature of reality. This interpretation enriches the ongoing scholarly discussion about Jane Eyre in light of its relevance to discussions of gender, power dynamics, and societal change.